Habitat use by Atherinella brasiliensis (Quoy & Gaimard, 1825) in intertidal zones of a subtropical estuary, Brazil - Barbara Maichak de Carvalho; Henry Louis Spach (Acta Scientiarum. Biological Sciences, 2015)
Habitat use is different along the ontogenetic development of some species and may be influenced by environmental parameters. This study described the interaction of Atherinella brasiliensis caught in intertidal areas of the Paranaguá Estuarine Complex with environmental parameters. We caught 10024 individuals between August 2010 and July 2011, with total mean length of 44.32 mm (SD ± 25.37 mm), variation range between 12 and 142 mm, and weight between 0.01 and 73 g, averaging 1.35 g (SD ± 2.66 g) and ages estimated between < 1 and 22 months. Significant differences were detected between sectors and periods for number of individuals and weight at capture, with higher mean values in the mean sector during the rainy period. The spatial and temporal distribution of ages was statistically different, individuals between < 1 and 3 months were more abundant in the sector 2 during the rainy period, and individuals older than 7 months were evenly distributed throughout the sampling area, and with higher mean abundance at the beginning and end of the dry period. Environmental variables that most influenced the distribution of age classes were temperature and salinity.